Analisis Brand Image terhadap Minat Mahasiswa Masuk Perguruan Tinggi menggunakan Metode Cochrand Q Test dan Marketing Mix (Studi Kasus: Mahasiswa S-1 Teknik Industri UIN Suska Riau) - Tiyandari, Reni Sulis; Kusumanto, Ismu; Suherman, Suherman; Umam, Muhammad Isnaini Hadiyul; Nofirza, Nofirza (Universitas Batanghari Jambi, 2025)
This research aims to analyze the factors that form the brand image of the Department of Industrial Engineering, UIN Suska Riau and design promotional strategies using the Cochran test and Marketing Mix methods. Data was obtained from 100 respondents through a questionnaire. The research results show that there are significant differences between the attributes tested, with the Q value being greater than the X² table value in all tests. The main factors that shape a brand image include reputation, accreditation, teaching staff, quality of education, and student comfort. 7P-based promotional strategy to improve brand image and attract more students.